Murder most fowl - Maxwell, Edith (Maxwell, Edith. Local foods mystery., 2016)
"Spring may be just around the corner, but a cold-blooded killer has put the big chill on the residents of Westbury, Massachusetts. It looks like organic farmer-turned-sleuth Cam Flaherty will have to set aside her seedlings for the time being as she tills the soil for clues in the mysterious death of a local poultry maven. With the weather getting warmer, Cam should be spending her days pruning blueberry bushes and taking care of the new batch of chicks that just hatched. But murder knows no season. So when her fellow fowl-raiser Wayne Laitinen is found dead at his breakfast table one morning, Cam must put down her trimming shears and put on her crime-solving hat. The kind-hearted chicken farmer didn't have any enemies--or did he? A wealthy financier has been working hard to convince him to sell her his land, while a group of animal rights activists recently vandalized his property. Money troubles were threatening to sink his marriage. And a thirty-year-old scandal was driving a wedge between him and one of his oldest friends. Murder, blackmail, cover-ups. There's a fox in the hen house. But where? With some help from her off-again, on-again flame, police detective Pete Pappas, Cam will have to crack this case before Wayne's killer flies the coop forever."--Dust jacket flap.